Description of the Anxiety Level of Chronic Kidney Failure Patients Undergoing Hemodialysis at the Haji Adam Malik General Hospital Medan In 2021 - Agnes Yuditia Hutagaol; Magda Siringo-ringo; Nagoklan Simbolon (Institute of Computer Science (IOCS), 2022)
Chronic renal failure (CKD) is a disorder of kidney function in regulating fluid and electrolyte balance and loss of power in metabolic processes. Hemodialysis is a medical procedure performed for chronic kidney failure. Hemodialysis can have an impact on the patient's psychology, one of which is anxiety which will affect physical, social and spiritual health. Several factors that cause anxiety in patients undergoing hemodialysis include age, gender, education level, patient experience undergoing treatment, length of therapy. The purpose of this study was to describe the level of anxiety based on the characteristics of patients with chronic kidney failure undergoing hemodialysis at H. Adam Malik Hospital Medan in 2021. This study was a descriptive study. consecutive sampling which amounted to 74 respondents according to the inclusion criteria. Data analysis used univariate analysis. The research instrument uses a questionnaireZung Self- Rating Anxiety Scale (ZSAS). The study showed that all chronic kidney failure patients undergoing hemodialysis were at a mild anxiety level of 75.7%, which was mostly experienced by the elderly group aged 46-65 years 69.6%, male 73.2%, secondary education 48,2%, undergoing hemodialysis >6 months 92.9%, private employee work 25.0%, and type of financing BPJS 100%. This study illustrates that the anxiety level of chronic kidney failure patients undergoing hemodialysis is influenced by characteristics such as age, gender, education, duration of hemodialysis, occupation and type of financing. It is recommended that hospitals provide services that can minimize the anxiety level of hemodialysis patients.